2018
DOI: 10.1038/s41598-018-29354-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-lightweight superconducting wire based on Mg, B, Ti and Al

Abstract: Actually, MgB2 is the lightest superconducting compound. Its connection with lightweight metals like Ti (as barrier) and Al (as outer sheath) would result in a superconducting wire with the minimal mass. However, pure Al is mechanically soft metal to be used in drawn or rolled composite wires, especially if applied for the outer sheath, where it cannot provide the required densification of the boron powder inside. This study reports on a lightweight MgB2 wire sheathed with aluminum stabilized by nano-sized γ-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The set of single-core MgB 2 wires has been made by identical IMD process. The metallic tubes with purity 99.9% of diameter 9.0/6.2 mm were used for outer sheath: from Cu (named Cu-A) and from Al with 1.5 vol % Al 2 O 3 metal matrix composite (named Al-B) and Al with 3.1 vol % Al 2 O 3 (named Al-C) prepared by powder metallurgy [14][15][16] are described by table 1. HV0.05 is the micro-hardness measured for these sheath materials in as-deformed state.…”
Section: Methodsmentioning
confidence: 99%
“…The set of single-core MgB 2 wires has been made by identical IMD process. The metallic tubes with purity 99.9% of diameter 9.0/6.2 mm were used for outer sheath: from Cu (named Cu-A) and from Al with 1.5 vol % Al 2 O 3 metal matrix composite (named Al-B) and Al with 3.1 vol % Al 2 O 3 (named Al-C) prepared by powder metallurgy [14][15][16] are described by table 1. HV0.05 is the micro-hardness measured for these sheath materials in as-deformed state.…”
Section: Methodsmentioning
confidence: 99%
“…These Al 2 O 3 particles which act as dispersoids in the Al matrix, will influence the microstructure (grain structures) slightly differently. On annealing, the bigger Al 2 O 3 dispersoids may impose smaller stabilizing effect on the low angle grain boundaries of Al [10]. The microstructural features which will be slightly different in the case of can affect the mechanism of the critical current flowing through the wire, and hence gets reflected on the I c -B curve which has a slightly different slope than the other two wires.…”
Section: Critical Current and I-v Characteristics Of Mgb 2 Wiresmentioning
confidence: 99%
“…Additionally, Nb may not be a good option to be used as a barrier with Al + Al 2 O 3 sheath because of higher reaction kinetics between Nb and Al [7]. On the other hand, the sufficiently ductile Ta is reported to show a minimal reactivity with Mg [10]. Few authors of this article have found that Ti offers the best core uniformity and the highest powder density prior to the heat treatment among the others [19], and produces a superconducting wire which is considerably lighter when combined with the (Al + Al 2 O 3 ) stabilizer sheath [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, round MgB chemically doped wires are of particular importance, not only due to their superior and upper critical field, , but because the powder-in-tube process allows an easy manufacturing of multicore (a.k.a. multifilamentary) wires 9 , 10 , as precursors of high-power AC/DC applications such as, power transmission cables 11 13 , rotary machines 14 17 , energy-storage devices 18 , MRI cryogen-free magnets 19 21 , fusion reactors 22 , and the large scale commercialization of high-current SC links for CERN 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%